The abandonment of the garden or the delimitation of a new narrative space in the novels of Antonio Gala: The journey to the body - Iona Pavel (Global Writing Academica Researching and Publishing, 2024)
The aim of this work is to study the female body as a narrative space in the novels by Antonio Gala. In his novels the human body is the only setting in which the characters see themselves capable of creating and developing their own identity.